Policy towards combining work and eldercare - Jurek, Łukasz (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The issue of combining work and eldercare is currently a priority for social policy. This problem is gaining importance, mainly is due to changes in the demographic structure. The increase in the share of oldest old people causes, in one hand, increase in demand for care services, and on the other hand the need for professional activation of different groups, including women, who are natural caregivers for the elderly. In this situation it is necessary to create solutions that allow effective combining work and care responsibilities.The purpose of this article is to present the main issues related to working people caring for elderly family members, as well as actions taken to reduce these problems.